A denitration catalyst suitable for alkali furnaces, a preparation method and application thereof
By introducing pore modifiers and modified components onto the TiO2 support, the pore structure and active sites were optimized, solving the problems of water poisoning and alkali metal poisoning of VW-Ti catalyst under high humidity conditions in alkali furnaces, and improving the stability and denitrification efficiency of the catalyst.
Patent Information
- Application Number
- CN202610531417.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-21
- Publication Date
- 2026-07-24
AI Technical Summary
Existing VW-Ti catalysts are prone to water poisoning and alkali metal poisoning under high humidity conditions in alkaline furnaces, resulting in decreased denitrification efficiency and shortened lifespan, as well as insufficient low-temperature activity.
By introducing pore-modifying agents such as methyltrichlorosilane, Ce-modifying components, and La-modifying components onto the TiO2 support, the pore structure is optimized, the selective adsorption of oxygen vacancies and NH3 is enhanced, sacrificial sites resistant to water and alkali metals are formed, and the stability of the catalyst is improved.
The stability and denitrification efficiency of the catalyst were improved in a high-humidity and high-alkali metal environment, the problems of pore blockage and active site coverage were solved, and the catalyst life was extended.
Smart Images

Figure CN122441431A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of denitrification catalyst technology, specifically relating to a denitrification catalyst suitable for alkali furnaces, its preparation method, and its application. Background Technology
[0002] Alkali furnaces are core equipment in industries such as pulp and paper making and chemical processing. Their flue gas is characterized by medium and low temperature (150~250℃), high water content (20~30%), high alkali metal (K / Na) content, and high dust content, which makes them the core challenge for the application of selective catalytic reduction (SCR) denitrification technology. Among them, catalyst water poisoning caused by high humidity, active site poisoning caused by high alkali metal, and insufficient activity at low temperature are the three key problems that restrict denitrification efficiency and catalyst lifespan.
[0003] The VW-Ti system is currently the mainstream catalyst system for medium- and low-temperature SCR denitrification, but it has significant drawbacks under high-humidity conditions in alkali furnaces: First, the catalyst contains many micropores smaller than 4 nm, which easily lead to capillary condensation, causing water molecules to remain trapped in the pores and become difficult to desorb, resulting in pore blockage. Second, water molecules and NH3 compete for adsorption at the catalyst's active sites, occupying the acidic active sites of the VW-Ti system, preventing NH3 from being effectively adsorbed and activated, thus significantly reducing denitrification efficiency. Third, under low-temperature and high-humidity conditions, the active sites of the VW-Ti system are not stable enough and are prone to hydration degradation. Fourth, alkali metals tend to neutralize acidic sites and cover active centers, resulting in insufficient stability of active sites at low temperatures, all of which contribute to a significant decrease in denitrification efficiency and a shortened catalyst life. Summary of the Invention
[0004] The technical problem to be solved by this invention is how to provide a denitrification catalyst that is resistant to water poisoning and alkali metal poisoning.
[0005] The present invention solves the above-mentioned technical problems through the following technical means:
[0006] The first aspect of this invention provides a denitrification catalyst suitable for alkali furnaces, comprising the following raw materials: TiO2 support, pore modifier, vanadium precursor, tungsten precursor, Ce-modified component, and La-modified component; based on the mass of the TiO2 support, the mass percentage of the pore modifier is 3-7%, the mass percentage of the vanadium precursor is 1-3%, the mass percentage of the tungsten precursor is 1-7%, the mass percentage of the Ce-modified component is 1-5%, and the mass percentage of the La-modified component is 0.5-1.5%; the pore modifier is methyltrichlorosilane.
[0007] Beneficial effects: This invention uses VW-Ti as the base system. By modifying the pore structure of the TiO2 support, the pore size structure of the TiO2 support is optimized, eliminating capillary condensation and achieving hydrophobicity. Ce modification of the VW-Ti system enhances the selective adsorption of oxygen vacancies and NH3. La modification of the VW-Ti system enhances the acidity of the catalyst and provides alkali metal sacrificial sites. These three factors work synergistically to solve the problems of water poisoning, alkali poisoning, and insufficient activity at low temperatures.
[0008] Preferably, the vanadium precursor is ammonium metavanadate; the tungsten precursor is ammonium metatungstate; the Ce modifying component is cerium salt; and the La modifying component is lanthanum salt.
[0009] Preferably, the Ce-modifying component is cerium nitrate; the La-modifying component is lanthanum nitrate.
[0010] More preferably, based on the mass of the TiO2 support, the mass percentage of the pore modifier is 5%, the mass percentage of the Ce modified component is 3%, and the mass percentage of the La modified component is 1%.
[0011] Beneficial effects: Under this ratio, the pore size of the denitrification catalyst is mainly distributed in the range of 8~20nm mesopores, and the proportion of <4nm micropores is reduced to less than 5%. The denitrification performance of water resistance, alkali resistance and low temperature is optimal.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned denitrification catalyst suitable for alkali furnaces, comprising the following steps: TiO2 support is mixed with water to obtain a slurry, and methyltrichlorosilane solution is added to it to react and obtain TiO2 slurry. Vanadium precursor, tungsten precursor, Ce modified component and La modified component are added to TiO2 slurry in proportion, and the mixture is stirred, shaped, dried and calcined to obtain denitrification catalyst.
[0013] More preferably, the TiO2 support is dried before mixing.
[0014] More preferably, the drying process is carried out at a temperature of 110-120°C for 3-4 hours.
[0015] Preferably, the mass fraction of the methyltrichlorosilane solution is 10-15%.
[0016] Preferably, the mass fraction of the methyltrichlorosilane solution is 10-15%.
[0017] Preferably, the reaction temperature is 40~60℃ and the reaction time is 2~3h.
[0018] More preferably, hydrochloric acid is used to adjust the pH to 3-5 during the reaction.
[0019] Preferably, the molding process is a honeycomb molding process.
[0020] More preferably, the formed opening ratio is 65-75% and the wall thickness is 0.8-1.0 mm.
[0021] Preferably, the drying temperature is 110~120℃ and the drying time is 6~7h.
[0022] Preferably, a stepped roasting method is adopted, and the specific operation is as follows: the temperature is increased to 250℃ at a rate of 5℃ / min and held for 2 hours, then the temperature is increased to 450~500℃ and held for 4 hours, and then naturally cooled to room temperature.
[0023] The third aspect of the present invention provides the application of the above-mentioned denitrification catalyst suitable for alkali furnaces, which is used in the SCR denitrification system of alkali furnaces.
[0024] Preferably, the denitrification reaction temperature is 150~250℃.
[0025] Preferably, the water content of the flue gas in the alkali furnace is 20-30%, and the NH3 / NO3 ratio is [missing information]. X The molar ratio is 1.0~1.2.
[0026] Beneficial effects: The denitrification catalyst of the present invention can withstand high concentrations of alkali metal flue gas and can offset some of the competitive adsorption of water molecules and the influence of alkali metals.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention modifies the VW-Ti system using Ce and La, wherein the Ce-modifying component exists in the form of CeO2. 4+ / Ce 3+ The redox cycle enhances the oxygen migration ability of the denitration catalyst, optimizes the distribution of acidic sites, and improves the selective adsorption of NH3. The La-modified component exists in the form of La2O3, which further enhances the surface acidity, stabilizes the crystal phase structure of the denitration catalyst, preferentially captures alkali metals, forms alkali metal sacrificial sites, and synergistically improves the stability of the denitration catalyst with Ce.
[0028] 2. Methyltrichlorosilane covalently bonds with the hydroxyl groups on the TiO2 support surface, sealing hydrophilic sites and simultaneously regulating pore size distribution to reduce water-accumulating micropores. Residual organic matter is removed through calcination, promoting the formation of active substances and stabilizing the bonding of modifiers. The denitrification catalyst is honeycomb-shaped, with pore density and wall thickness suitable for the high dust characteristics of alkali furnace flue gas. Furthermore, the preparation process is simple, highly industrially operable, and requires no special equipment.
[0029] 3. This invention achieves optimal performance synergy by precisely optimizing the ratio of methyltrichlorosilane, Ce-modifying components, and La-modifying components, thus avoiding excessive addition that covers active sites or insufficient addition that leads to modification failure. Attached Figure Description
[0030] Figure 1 These are pore size distribution diagrams of the denitrification catalysts prepared in Example 1 and Comparative Example 1 of the present invention; Figure 2 This is a graph showing the water resistance test results of the denitrification catalyst prepared in Example 1 of this invention. Detailed Implementation
[0031] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0032] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.
[0033] Unless otherwise specified in the embodiments, the techniques or conditions described in the literature in this field or in accordance with the product manual may be followed.
[0034] Example 1 This embodiment provides a method for preparing a denitrification catalyst, the specific steps of which are as follows: Pore modification: The anatase TiO2 support was dried in a 120℃ drying oven for 4 hours to remove physically adsorbed water. 5 kg of methyltrichlorosilane was dissolved in ethanol to obtain a 12% (w / w) methyltrichlorosilane solution.
[0035] Then, 100 kg of anatase TiO2 support was mixed with 300 L of deionized water to form a slurry. Methyltrichlorosilane solution was slowly added dropwise to the slurry. The pH was adjusted to 4 with hydrochloric acid under stirring at 50 °C and 300 r / min. The reaction was kept at this temperature for 2.5 h to obtain TiO2 slurry.
[0036] Catalyst preparation: 3 kg of cerium nitrate hexahydrate, 1 kg of lanthanum nitrate hexahydrate, 2 kg of ammonium metavanadate, and 5 kg of ammonium metatungstate were added to TiO2 slurry and stirred for 4 h. Then, the mixture was formed using a honeycomb molding process with an open porosity of 65-75% and a wall thickness of 0.8-1.0 mm. The mixture was dried at 110℃ for 6 h, and then heated to 250℃ at 5℃ / min and held for 2 h. The temperature was then further increased to 420℃ and held for 4 h. The mixture was then naturally cooled to room temperature to obtain the 1-1# denitration catalyst.
[0037] Example 2 This embodiment provides a method for preparing a denitrification catalyst. The difference between this embodiment and Example 1 is that 5 kg of methyltrichlorosilane is replaced with 3 kg to obtain denitrification catalyst 1-2#.
[0038] Example 3 This embodiment provides a method for preparing a denitrification catalyst. The difference between this embodiment and Example 1 is that 5 kg of cerium nitrate hexahydrate is replaced with 3 kg to obtain denitrification catalyst 1-3#.
[0039] Example 4 This embodiment provides a method for preparing a denitrification catalyst. The difference between this embodiment and Example 1 is that 1 kg of lanthanum nitrate hexahydrate is replaced with 1.5 kg to obtain denitrification catalysts 1-4#.
[0040] Comparative Example 1 This comparative example provides a method for preparing a denitrification catalyst. The difference between this comparative example and Example 1 is that no methyltrichlorosilane solution was added, and the catalyst was prepared using a slurry to obtain the 2-1# denitrification catalyst.
[0041] Comparative Example 2 This comparative example provides a method for preparing a denitrification catalyst. The difference between this comparative example and Example 1 is that cerium nitrate hexahydrate was not added, resulting in the 2-2# denitrification catalyst.
[0042] Comparative Example 3 This comparative example provides a method for preparing a denitration catalyst. The difference between this comparative example and Example 1 is that lanthanum nitrate hexahydrate was not added, resulting in denitration catalyst #2-3.
[0043] Comparative Example 4 This comparative example provides a method for preparing a denitrification catalyst. The difference between this comparative example and Example 1 is that the final calcination temperature of 420℃ is replaced with 380℃ to obtain denitrification catalysts 2-4#.
[0044] Experimental Example 1. Catalyst water resistance test (1) The pore size distribution diagrams of the denitration catalysts prepared in Example 1 and Comparative Example 1 are shown in the figure. Figure 1 As shown in the figure, the micropore-mesopore distribution of the 2-1# denitration catalyst is a single-peak distribution dominated by 4 mm micropores, while the micropore-mesopore distribution of the 1-1# denitration catalyst is a single-peak distribution dominated by 8~20 nm mesopores. This indicates that after modifying the TiO2 support with methyltrichlorosilane, the pore structure of the denitration catalyst is significantly regulated, which can effectively eliminate the capillary water absorption effect of micropores and improve the water resistance stability of the denitration catalyst.
[0045] (2) The denitrification catalyst prepared in the example was subjected to a water resistance test at 170°C. The test conditions were: denitrification temperature of 170°C, flue gas water content of 20-40%, and NO content of 100-200%. x Concentration of 500 mg / Nm³, NH3 / NO x =1.1, the flue gas velocity in the catalyst pores is 4.6 m / s, the results are as follows Figure 2 As shown.
[0046] according to Figure 2 It can be seen that the denitrification catalyst prepared in Example 1 exhibits an activity decrease of approximately 3.2% at a water content of 20%, and only a 15% activity decrease at a water content of 30%. Combined with the design of the denitrification catalyst dosage, the denitrification catalyst prepared in this invention can meet the requirements for water poisoning-resistant denitrification at temperatures ranging from 150°C to 250°C.
[0047] 2. Catalyst denitrification performance test (1) Simulated alkali metal poisoning of catalyst: The denitration catalysts prepared in Examples 1-4 and Comparative Examples 1-4 were subjected to alkali metal poisoning operation as follows: 1 wt% K2O was dissolved in deionized water to obtain a solution, the catalyst to be tested was immersed in the solution, and the solution was allowed to stand at room temperature for 6 h, then dried at 110 °C for 6 h, and kept at 450 °C for 2 h to decompose KNO3 into K2O, thus obtaining the alkali metal poisoned catalyst.
[0048] (2) The catalyst poisoned by alkali metals was placed in an alkali furnace and tested under simulated denitrification conditions. The test conditions were: denitrification temperature of 170℃, flue gas water content of 20%, and NO content of 10%. x Concentration 500 mg / Nm³, NH3 / NO x The molar ratio was 1.1, and the system was run continuously for 720 hours. The denitrification efficiency and activity decay rate were tested, and the results are shown in Table 1.
[0049] Table 1. Performance test results of the catalyst
[0050] As shown in Table 1, Example 1 is the optimal example. The initial denitrification efficiency of the 1-1# denitrification catalyst is 94%, and it still reaches 91% after 720 hours, with an activity decay rate of only 3.2%. Examples 2-4 show better overall performance compared to Comparative Examples 1-4.
[0051] Comparative Example 1, lacking pore modification, exhibited a high proportion of hydrophilic sites and micropores in its denitrification catalyst, leading to severe water poisoning and significant activity degradation under high humidity conditions. Comparative Example 2, lacking Ce-modifying components, showed a sharp decline in oxygen migration and NH3 selective adsorption capacity, resulting in extremely poor low-temperature activity and resistance to water and alkalis. Comparative Example 3, lacking La-modifying components, lacked alkali metal sacrificial sites, leading to rapid neutralization of acidic active sites by alkali metals and accelerated activity degradation. Comparative Example 4, due to excessively low calcination temperature, resulted in insufficient crystallization of the active material and unstable bonding of the modifier, significantly degrading the structure and performance of the denitrification catalyst.
[0052] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A denitrification catalyst suitable for alkali furnaces, characterized in that, Including the following raw materials: The composition comprises TiO2 support, pore modifier, vanadium precursor, tungsten precursor, Ce modifier, and La modifier. Based on the mass of the TiO2 support, the mass percentages of the pore modifier, vanadium precursor, tungsten precursor, Ce modifier, and La modifier are 3-7%, 1-3%, 1-7%, 1-5%, and 0.5-1.5%, respectively. The pore modifier is methyltrichlorosilane.
2. The denitrification catalyst suitable for alkali furnaces according to claim 1, characterized in that, The vanadium precursor is ammonium metavanadate; the tungsten precursor is ammonium metatungstate; the Ce modification component is cerium salt; and the La modification component is lanthanum salt.
3. The denitrification catalyst suitable for alkali furnaces according to claim 1, characterized in that, The Ce-modifying component is cerium nitrate; the La-modifying component is lanthanum nitrate.
4. A method for preparing a denitrification catalyst suitable for an alkali furnace as described in any one of claims 1-3, characterized in that, Includes the following steps: TiO2 support is mixed with water to obtain a slurry, and methyltrichlorosilane solution is added to it to react and obtain TiO2 slurry. Vanadium precursor, tungsten precursor, Ce modified component and La modified component are added to TiO2 slurry in proportion, and the mixture is stirred, shaped, dried and calcined to obtain a denitrification catalyst suitable for alkali furnace.
5. The method for preparing a denitrification catalyst suitable for an alkali furnace according to claim 4, characterized in that, The mass fraction of the methyltrichlorosilane solution is 10-15%, the reaction temperature is 40-60℃, and the reaction time is 2-3 hours.
6. The method for preparing a denitrification catalyst suitable for an alkali furnace according to claim 4, characterized in that, The product is formed using a honeycomb molding process, and the drying temperature is 110~120℃ for 6~7 hours.
7. The method for preparing a denitrification catalyst suitable for an alkali furnace according to claim 4, characterized in that, A stepped calcination method is adopted, and the specific operation is as follows: the temperature is increased to 250℃ at a rate of 5℃ / min and held for 2 hours, then the temperature is increased to 450~500℃ and held for 4 hours, and then naturally cooled to room temperature.
8. The application of a denitrification catalyst suitable for alkali furnaces prepared by a method according to claims 1-3 or any one of claims 4-7, characterized in that, The denitrification catalyst suitable for alkali furnaces is used in the SCR denitrification system of the alkali furnace.
9. The application of the denitrification catalyst suitable for alkali furnaces according to claim 8 in alkali furnaces, characterized in that, The denitrification reaction temperature is 150~250℃.
10. The application of the denitrification catalyst suitable for alkali furnaces according to claim 8 in alkali furnaces, characterized in that, The water content of the flue gas in the alkali furnace is 20-30%, and the NH3 / NO content is... X The molar ratio is 1.0~1.2.